Bioactivities and Mechanism of Actions of Dendrobium officinale: A Comprehensive Review - Xu, Xiaoyu; Zhang, Cheng; Wang, Ning; Xu, Yu; Tang, Guoyi; Xu, Lin; Feng, Yibin (Oxidative medicine and cellular longevity, 2022)
Dendrobium officinale has a long history of being consumed as a functional food and medicinal herb for preventing and managing diseases. The phytochemical studies revealed that Dendrobium officinale contained abundant bioactive compounds, such as bibenzyls, polysaccharides, flavonoids, and alkaloids. The experimental studies showed that Dendrobium officinale and its bioactive compounds exerted multiple biological properties like antioxidant, anti-inflammatory, and immune-regulatory activities and showed various health benefits like anticancer, antidiabetes, cardiovascular protective, gastrointestinal modulatory, hepatoprotective, lung protective, and neuroprotective effects. In this review, we summarize the phytochemical studies, bioactivities, and the mechanism of actions of Dendrobium officinale, and the safety and current challenges are also discussed, which might provide new perspectives for its development of drug and functional food as well as clinical applications.